Spiraling or self-correcting discrimination: A multi-armed bandit approach - Arjada Bardhi; Yingni Guo; Bruno Strulovici (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2019)
Can workers from social groups of comparable productivities obtain comparable employment opportunities in the long run? We model dynamic hiring and employer learning via a general Poisson multi-armed bandit framework. Breakdown environments that reveal on-the-job mistakes rather than successes give a large advantage to marginally more productive groups. Breakthrough environments, in contrast, guarantee comparable payoffs to comparable groups. This insight is robust to various sources of across-groups heterogeneity, belief misspecification by employers, and varying degrees of labor demand scarcity. Equal access to productivity investment only enhances prior differences across groups.
Keywords: D83; J71; C73; 330; breakdown learning; breakthrough learning; endogenous bandits; spiraling property; self-correcting property; ranking multiplicity